Engineering Properties of Epoxy Polymer Cement Concrete Reinforced with Glass Fibers - Cheng, Hock Tian (2011)

(untitled)
Previous research on mechanical properties and fracture behavior of concrete reinforced with glass fibers and some results are presented. It is well known that high strength concrete displays a brittle behavior and less tough characteristics than normal strength concrete. This type of behavior can be enhanced by incorporating various types of fibers or various types of matrix which lead to better mechanical properties and fracture properties. In this study, an experimental study on epoxy polymer cement concrete reinforced with glass fibers and steel fibers both used at a relatively low volume fraction is presented. Polymer concrete is a composite material formed by polymerizing a monomer and aggregate mixture. The polymerized monomer acts as the aggregates binder. In this research, the polymer is epoxy resin mixed with cement and aggregates as used in the foundry industry. Initiators and promoters are added to the resin prior to its mixing with the inorganic aggregates to initiate the curing reaction. Compressive, splitting, three-point bending and impact test methods have been used to characterize reinforced concrete materials and the results are analyzed statistically. Fracture behavior of steel fibers and glass fibers reinforced epoxy polymer cement concrete is investigated. This is a direct method to calculate two size independent fracture parameters, i.e., the critical stress intensity factor, KIC and the Crack Tip Opening Displacement (CTOD). Beams with central notch, fewer than three points bending using attached clip gauge to measure the CTOD are tested. The glass fibers were also pre-treated with silane to improve the adhesion between fibers and resin and fracture properties